IMPLEMENTATION OF THE PROSPEROUS FAMILY CARD PROGRAM IN KALA KEMILI VILLAGE, CENTRAL ACEH REGENCY - Indah Sepira; Ahmad Yani; Arinanda; Muklir; Risna Dewi (RADJA PUBLIKA, 2025)
This study aims to analyze the implementation of the Prosperous Family Card (PFC) Program in Kala Kemili Village, Central Aceh Regency, and to identify the factors contributing to its mistargeting during implementation. The KKS program is one of the government's strategic instruments to alleviate poverty by distributing non-cash social assistance to poor and vulnerable families. The findings indicate that the number of KKS recipients in Kala Kemili Village, Central Aceh Regency, is relatively high. There are 400 KKS recipients out of a total of 700 households in the village. This research adopts a qualitative approach with a descriptive method. The results show that the implementation of the KKS program in Kala Kemili Village has not been fully effective. Several key obstacles identified include a lack of public outreach, inaccurate beneficiary data—such as recipients who have passed away or relocated—and limited facilities and resources at the village level. The study recommends enhancing data validation, increasing the capacity of village officials, and strengthening coordination among relevant agencies to support the accurate targeting of the KKS program.